Road to earthquake mitigation: Lesson learnt from the Yogyakarta earthquake 2006 - Subagyo Pramumijoyo (Journal of Applied Geology, 2009)
At early in the morning of May 27, 2006, people of Yogyakarta was stroke by earthquake and mostly heavily damaged building are in lowland or Yogyakarta depression where is occupied by the Young Merapi sediments. The magnitude of earthquake is Mw = 6.2 and USGS rapid moment tensor shows that this earthquake was due to strike-slip fault movement.Seismic history of Yogyakarta area shows that Yogyakarta was stroke by several earthquakes with different epicenter location. At least two earthquakes stroke the area, that is in 1876 and 1943. The damages are similar to the damages of actual earthquake. Yogyakarta depression is mostly covered by Young Merapi sediments that consist of tuff, volcanic ash, breccias, agglomerate and lava with Quaternary in age. The thickness of this sediment is up to 100 m.Our reactive work was to establish firstly zone of damage. For this purpose, we made aerial photograph along the most damaged area. In the same time one of our teams go to the field to measure the cracks, and the other teams to observe liquefaction, hydro geologic measurement, and observation on landslide induce by earthquake. Secondly, we must understand the soil properties and its thickness, because in seismic history it was a similar damage on the same area due to earthquakes however the earthquake epicenters were different. For this purpose we utilize the method of micro-tremors. We also made some drilling until 60 m each, measuring seismic velocity on bore hole, and magneto telluric measurement. We also have helped by Kyushu University in installing micro seismic net work. The research was followed by either undergraduate and graduate students. Fortunately our research was financed by AUN/Seed Net – JICA. Some of the results were published in a book entitled The Yogyakarta Earthquake of May 27, 2006. Another outcome is the Maps of Microzonation and Earthquake Hazard of Bantul Area that dedicated to Bantul people.Based on aerial photograph observation and field observation on Bantul Regency, especially along the Opak River, and to Wonosari to the East, there was no surface ruptures, so there is no fault on surface. Interpretation of aftershock data was showing the difference cluster. There is still open problem in determining either epicenter or aftershock location. The damage building was interpreted as due to its geologic setting, non engineered building, and close to epicenter of earthquake. This heavily damaged building are located on the Young Merapi sediments at Bantul Regency and lake deposits at Gantiwarno and Bayat area where it can amplify the surface seismic wave. It implies that Peak Ground Acceleration according to Indonesian National Standard should be modified in Yogyakarta area.Keywords: Earthquake, seismic, epicenter, micro-tremor, microzonation